2015
DOI: 10.1002/app.42492
|View full text |Cite
|
Sign up to set email alerts
|

Segmented polyurethane elastomers by nonisocyanate route

Abstract: Novel segmented polyurethane elastomers were successfully synthesized by a nonisocyanate route using dicyclic carbonates as precursors for both soft and hard segments. The hard segment was prepared from the dicyclic carbonate of bisphenol A and mxylylenediamine as chain extender. The soft segment was poly(tetramethylene ether) glycol of molecular weight 1000. Three polyurethanes with different morphologies were made with soft segment concentration of 70, 50, and 30%. Method of synthesis consisted in preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 25 publications
4
40
0
Order By: Relevance
“…The observed increase in tensile strength also caused the phase separation between the hard and soft segments of the matrix, [37] which is stimulated by the presence of nanofiller. It was found that the TS B values for the composites containing 1 and 2 wt.% of GNP were higher or equal to that of the reference material.…”
Section: Evaluation Of Mechanical Propertiesmentioning
confidence: 99%
“…The observed increase in tensile strength also caused the phase separation between the hard and soft segments of the matrix, [37] which is stimulated by the presence of nanofiller. It was found that the TS B values for the composites containing 1 and 2 wt.% of GNP were higher or equal to that of the reference material.…”
Section: Evaluation Of Mechanical Propertiesmentioning
confidence: 99%
“…9). Generally, an increase in tensile strength also resulted from phase separation (Nanclares et al 2015) between the soft and hard segments of the matrix which is favored by the presence of MCC. It was observed that for the higher MCC contents the differences between the TS b values were insignificant, i.e.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…While extensive research has been done on PHU synthesis, relatively little work has focused on nanophase-separated PHUs as thermoplastic elastomer [53,54]. Only one study has contributed to understanding the role of hydroxyl groups in modifying the properties of thermoplastic PHU elastomer in comparison to analogous, isocyanate-based thermoplastic PU elastomers (TPUs) [54].…”
Section: Introductionmentioning
confidence: 99%